2018
DOI: 10.1016/j.seizure.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparable indicators of therapeutic misconception between epilepsy or Parkinson’s disease patients between those with clinical trial experience and trial non-participants

Abstract: While most in our study agreed that patients should be asked to participate in CTs, only 15% of subjects had done so. The discrepancy between willingness to participate and recruitment figures could be minimised by improving knowledge of CTs and communication between patients and researchers. Additionally, the groups displayed comparable false CT-related assumptions, raising questions about whether these subjects fully understood the clinical research's ultimate goal and CT participants had given true informed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The scale has good internal consistency (Cronbach's alpha scores of 0.75-0.83) [15]. Adaptations of this scale have been used to assess therapeutic misunderstanding in PD and epilepsy [18,26,27]. High scores (e.g., agreement) on each subscale indicated that an individual may be at-risk for therapeutic misconception, misestimation, or optimism, respectively [15].…”
Section: Therapeutic Misunderstanding Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The scale has good internal consistency (Cronbach's alpha scores of 0.75-0.83) [15]. Adaptations of this scale have been used to assess therapeutic misunderstanding in PD and epilepsy [18,26,27]. High scores (e.g., agreement) on each subscale indicated that an individual may be at-risk for therapeutic misconception, misestimation, or optimism, respectively [15].…”
Section: Therapeutic Misunderstanding Scalementioning
confidence: 99%
“…Safety, Information Needs, Negative Expectations, and Patient Involvement (Cronbach's alpha scores of 0.64-0.73). This scale was developed with patients diagnosed with cancer or asthma, and adaptations of this scale have been used to assess trial attitudes in PD and epilepsy[18,[26][27][28]. The scores from the scale were interpreted as follows: high Positive Beliefs scores suggested that respondents held positive views about trials; high Safety scores suggested respondents assumed clinical trial safeguards are in place, high Information Needs scores suggested respondents required information regarding trials,…”
mentioning
confidence: 99%
“…One of the primary aspects that characterize apps in this category is providing access to research on the disorder in a manner that is acceptable and understandable to a lay audience [65]. There may be a variety of reasons for providing this information, including increasing understanding of and countering misperceptions about the course of a disease [66-68], increasing beliefs about negative consequences of inaction or dysfunctional action [69,70] and increasing beliefs that taking proper action will be beneficial [70,71].…”
Section: Methodsmentioning
confidence: 99%
“…One of the primary aspects that characterize apps in this category is providing access to research on the disorder in a manner that is acceptable and understandable to a lay audience [65]. There may be a variety of reasons for providing this information, including increasing understanding of and countering misperceptions about the course of a disease [66][67][68], increasing beliefs about negative consequences of inaction or dysfunctional action [69,70] and increasing beliefs that taking proper action will be beneficial [70,71].…”
Section: Education and Informationmentioning
confidence: 99%